Low-Loss Slot Waveguides with Silicon (111) Surfaces Realized Using Anisotropic Wet Etching - Debnath, Kapil; Khokhar, Ali Z.; Boden, Stuart A.; Arimoto, Hideo; Oo, Swe Zin; Chong, Harold M. H.; Reed, Graham T.; Saito, Shinichi (Frontiers in Materials, 2016)
We demonstrate low-loss slot waveguides on silicon-on-insulator (SOI) platform. Waveguides oriented along the (11-2) direction on the Si (110) plane were first fabricated by a standard e-beam lithography and dry etching process. A TMAH based anisotropic wet etching technique was then used to remove any residual side wall roughness. Using this fabrication technique propagation loss as low as 3.7dB/cm was realized in silicon slot waveguide for wavelengths near 1550nm. We also realized low propagation loss of 1dB/cm for silicon strip waveguides.